OTIMALISASI PENGGUNAAN SUMBERDAYA LAHAN SAWAH TADAH HUJAN MELALUI PENERAPAN POLA USAHATANI DI DESA REMBITAN KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Ibrahim Ibrahim; Nurtaji Wathoni; Broto Handoko (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2018)
ABSTRAK ABSTRACT In order to obtain maximum results in a farming system, especially farming in rainfed areas, where both planting and harvesting failure often occur, the determination or selection of crop and cropping patterns becomes important. Likewise, combining different types of crop and livestock farming in a particular farming pattern is an effort in order to increase the farmer's total income.This study aims to: (1) Identify the farming pattern or mixed farm applied by rainfed farmers; (2) Calculating the income of each farming pattern; (3) Optimalizing the rainfed farming in Rembitan Village, Pujut Sub-district. This research uses descriptive method. The analysis used are: income analysis, linear programming, and sensitivity analysis.The results showed that: (1) There are 10 farming patterns conducted by farmers in the rainfed areas of Rembitan Village, Pujut Sub-district, Central Lombok Regency; (2) The average total farming pattern income in the rainfed areas of Rembitan Village, Pujut Sub-district, Central Lombok Regency, which combines crop and livestock farming is Rp 12.263.596,00/year; (3) There are three recommended farming petterns activity in rainfed areas of 882 ha maximizing Rembitan Village revenue of Pujut Sub-district, Central Lombok Regency, Rp 20,649,455,129 per year with distribution, namely: X4 activity of 177,71 hectares (20,15 %); X7 of 145,633 hectares (16,51%); and X10 of 558,657 hectares (63,34%).